INDUSTRI MEDIA DALAM BUDAYA POPULAR KAJIAN SEMIOTIKA PIERCE PADA DRAMA KOREA SARANGHAE, I LOVE YOU - Venessa Agusta Gogali (Jurnal Komunikasi, 2016)
This research focuses on the meaning behind the Korean movie’ drama “Saranghae I Love You”. The acts in this movie are full of communication strategy to promote Korean culture. This research has purpose to know the representation of Korean popular cultural meaning. Representation can drive the rise of audience interpretation towards Korean drama “Saranghae I Love You”. To gain the data, this research uses qualitative approach with semiotic study from Pierce. Semiology’s analysis based on object as icon, symbol, and index. This research also uses concepts and theories of mass communication as confirmation data. The result states that the meaning behind Korean television drama “Saranghae I Love You”. Those meanings represent the trend of Korean culture or popular culture. Those icon of cultural trend is the movie’s setting. Those locations represent the interest and cultural trend in Korean public. Those icons are Myeong-Dong as icon of Korean shopping center. Namsan Tower as the icon of padlock love tour or love lock. Icon as the trend of Korean culture from fashion used by Jae Hyun and Asyu. Keywords: Popular culture, media industry, communication strategy, representation.